2011
DOI: 10.1007/s13238-011-1051-0
|View full text |Cite
|
Sign up to set email alerts
|

Conserved arginine residue in the membrane-spanning domain of HIV-1 gp41 is required for efficient membrane fusion

Abstract: Despite the high mutation rate of HIV-1, the amino acid sequences of the membrane-spanning domain (MSD) of HIV-1 gp41 are well conserved. Arginine residues are rarely found in single membrane-spanning domains, yet an arginine residue, R 696 (the numbering is based on that of HXB2), is highly conserved in HIV-1 gp41. To examine the role of R 696 , it was mutated to K, A, I, L, D, E, N, and Q.Most of these substitutions did not affect the expression, processing or surface distribution of the envelope protein (En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…An interesting observation correlated with the findings of Long, Y showed that Arginine (R) was most frequently associated amino acid (8). In all the 10 rules deduced Arginine was found to be associated with all the amino acids.…”
Section: Rules Framed For All the Classes Evaluated Togethersupporting
confidence: 84%
“…An interesting observation correlated with the findings of Long, Y showed that Arginine (R) was most frequently associated amino acid (8). In all the 10 rules deduced Arginine was found to be associated with all the amino acids.…”
Section: Rules Framed For All the Classes Evaluated Togethersupporting
confidence: 84%
“…The membrane spanning domain (MSD) of gp41 is of great interest as it is responsible for both anchoring gp41 in the bilayer and for playing a role in fusion, according to truncation studies [3,4]. Mutagenesis has also shown that the specific sequence of the twenty-seven residue MSD is important for membrane fusion [5–11]. The MSD houses the GXXXG motif, postulated to mediate transmembrane helical interactions, and the charged residues K681, R694, R705, and R707 (Table 1) [314].…”
Section: Introductionmentioning
confidence: 99%
“…Relatively large water defects have been studied by solid-state NMR and have also been observed in various simulation systems involving guanidinium ions, arginine analogs, and arginine containing transmembrane proteins (both β -barrels and α-helices) in various lipids [20,21,23,2631]. It has not been previously investigated if HIV-1 gp41 MSD displays a water defect in the native spike complex, but an arginine at position 694 (HXBc2 sequence) is required for full fusion [11,4]. Therefore, it stands to reason that if a water defect is present due to R694, the defect may play a role in fusion as well.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of these motifs during virus-cell fusion is not yet clear. Furthermore, a recent study showed that mutating the Arg residue within the intact protein did not affect the expression or location of Env, but rather, affected its fusion activity (38). …”
mentioning
confidence: 99%